KORELASI MEDIA SOSIAL INSTAGRAM DENGAN PRESENTASI DIRI MAHASISWA JURUSAN ILMU KOMUNIKASI UNIVERSITAS RIAU - Heny Gustina; Rumyeni Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
As the technologies develop nowadays, communication is not doing only by face-to-face, but also by using another internet intermediaries media, such as social media Instagram. Computer Mediated Communication theory or also well known as CMC theory is the latest theory in communication sciences development which is focused on how social media contributes in people communication and also describes how people have another world out of the real world, as we know it cyber world. The social media facilitates its users to present themselves. Self-presentation as one of the purpose of communication is an act in showing himself by a person to get a good image as what he expects.The method used in this research was quantitative method with explanatory survey, researcher collected data using questionnaires. The location of this research was in the Communication Science Department, University of Riau. The number of samples for this research were 155 respondents, sampling technique is using accidental sampling technique. To determine how much correlation between these two variables, researcher used the Pearson Product Moment Correlation analysis. As for the questionnaire data processing use Statistics Program Product Of Service Solutions (SPSS) windows version 20.In the result of this correlation between social media Instagram and self-presentation among the students of the Communication Sciences, University of Riau research shows that the correlation coefficient values obtained in this study is Y = 10,010 + 0619 X with the significance level of 0.001 which is smaller than α = 0.05. This result shows that there is correlation between social media Instagram and self-presentation among the students of Communication Sciences in University of Riau as much 58,8 % which is in moderate category. .Keywords: Social Media, Instagram, Adolescent, Self-Presentation, CMC Theory, Digital Communications, Social Life